Torsional Capacity of Composite Reinforced Concrete Beams with Stirrup Connectors - Witwit, Dolfocar Ali Usamah; Jasim, Nabeel Abdulrazzaq (Anbar Journal of Engineering Sciences, 2021)
New composite reinforced concrete beams, in which reinforced concrete component is connected to steel T-section, are proposed. The shear connection between the two components, the reinforced concrete and the T-section, is provided by the stirrups that are required for the reinforced concrete component to resist the applied shear. Experimental tests in addition to numerical analysis were conducted to determine the behaviour and strength of such beams under pure torsion. Full scale one conventional reinforced concrete beam, T1, and two composite reinforced concrete ones, T2 and T3, were tested. The degree of shear connection between the two components of beams T2 and T3 was changed by varying the number of stirrups which are used as shear connectors. The experimental results revealed approximately same torsional stiffness for the three beams at the uncracked concrete stage. The torsional strength of the composite reinforced concrete beams was greater than that of ordinary reinforced concrete one by 11% and 27% for beams T2 and T3, respectively. Three-dimensional finite element analysis was conducted using program ABAQUS. To model the shear connection in composite reinforced concrete beam, the stirrups were connected to the web of the steel T-section by springs at the location of the stirrups. Good agreement is obtained between the results of the experimental tests and the finite element analysis. The ratios of experimental results to those of finite element analysis for torsional strength are approximately one. Under the pure torsion loading the degree of shear connection is found to have no effect on torsional capacity of beams.